2011
DOI: 10.1128/jvi.00413-11
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Functional Domains and Complexes of the Two Nonstructural Proteins of Human Respiratory Syncytial Virus Contribute to Interferon Suppression and Cellular Location

Abstract: Human respiratory syncytial virus (RSV), a major cause of severe respiratory diseases, efficiently suppresses cellular innate immunity, represented by type I interferon (IFN), using its two unique nonstructural proteins, NS1 and NS2. In a search for their mechanism, NS1 was previously shown to decrease levels of TRAF3 and IKK, whereas NS2 interacted with RIG-I and decreased TRAF3 and STAT2. Here, we report on the interaction, cellular localization, and functional domains of these two proteins. We show that rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(137 citation statements)
references
References 44 publications
5
129
0
1
Order By: Relevance
“…When we tested the kinetics of the degradation, the pooled NSD fractions (#16-22, Figure 2A) were found to be active for only about 15 min ( Figure 2B). As we and others have recently found that a large portion of NS proteins are localized to the mitochondria [17,27], we speculated that mitochondrial association may be required for optimal NS functionality. However, as the purified NSD complex is ~300-750 kD in size, it cannot accommodate mitochondria; and thus, any mitochondria associated in vivo may have been dissociated from the complex during chromatography.…”
Section: Nsd Is Metastable and Its Activity Is Enhanced By The Presenmentioning
confidence: 83%
See 3 more Smart Citations
“…When we tested the kinetics of the degradation, the pooled NSD fractions (#16-22, Figure 2A) were found to be active for only about 15 min ( Figure 2B). As we and others have recently found that a large portion of NS proteins are localized to the mitochondria [17,27], we speculated that mitochondrial association may be required for optimal NS functionality. However, as the purified NSD complex is ~300-750 kD in size, it cannot accommodate mitochondria; and thus, any mitochondria associated in vivo may have been dissociated from the complex during chromatography.…”
Section: Nsd Is Metastable and Its Activity Is Enhanced By The Presenmentioning
confidence: 83%
“…We co-transfected A549 cells with NS1-and NS2-expressing plasmids [27,28], harvested cell-free extracts 20 h later using a non-denaturing buffer and subjected them to size fractionation using a Superdex 200 10/300 GL resin pre-calibrated with size markers, as described in the Materials and Methods. Substantial amounts of NS1/2 proteins (roughly 60% of the total) were found in the void volume, but we did not characterize the fraction of the void volume further due to its crude nature and the likely presence of multiple large cellular structures such as cell membranes and intracellular organelles.…”
Section: The Minimal Ns Degradasome Is a Heterogeneous Complex Of 300mentioning
confidence: 99%
See 2 more Smart Citations
“…The two NS proteins suppress both type I IFN induction and the IFN response pathways by interfering with various innate immunity actors such as RIG-I and STAT2. Recently, MAP1B was shown to interact with NS1 and NS2 and to contribute to the STAT2-degrading activity of NS2 (104). In the case of HIV infection, the viral transactivator Tat protein has been shown to contribute to neuronal damage observed in the brain of HIV-1 patients with neurological dysfunctions, by causing rapid proteasomemediated degradation of MAP2 leading to the collapse of cytoskeletal filaments, as well as aberrant splicing of tau (105,106).…”
Section: Resultsmentioning
confidence: 99%